Terjadinya Perizinan Perkawinan Poligami yang Tidak Berdasarkan Undang-Undang Perkawinan - Ferrary Utami; Hanafi Tanawijaya (Syntax Literate, 2023)
Polygamy marriage is where a man who has married a woman then remarries with another woman and has more than one wife, in Indonesia polygamy is possible if the person concerned gives permission to practice polygamy, or the application for polygamy permission must be linked to the permission of the first wife and Institutions certainly need to consider the application. The institutions that are imposed in granting the request are the Court and the Panel of Judges, unless meeting the requirements of the Court, I conclude whether the Petitioner will receive permission to enter into a polygamous marriage, the court will grant permission if the marriage has not reached the goal of marriage. Polygamous marriages cannot be used as an arena to measure one's religious obedience, in this case the more active the polygamist is considered the better his religious position, or the more patient a wife accepts polygamy, the more qualified her faith or considers her husband as sunnah. There have been many cases of a man who has more than one wife or is called polygamy, in this case the Judge of the West Jakarta Religious Court granted the request for permission to have polygamy on condition that he strengthens cumulatively and alternatives. If one of these conditions can be proven, then the court can give permission to practice polygamy and the court can grant it if these conditions have been met. The court must also investigate whether the wife really does not carry out the obligations of a wife, suffers from an incurable disease, or is unable to love offspring.